Risk factors contributing to weaning failure from continuous positive airway pressure to high flow nasal cannula in neonates with respiratory distress syndrome - Putra, Najih Rama Eka; Dadiyanto, Dwi Wastoro; Sahyuni, Riza; Rini, Arsita Eka; Muryawan, Heru; Suswihardhyono, Adhie Nur Radityo (Indonesian Pediatric Society, 2024)
Background Respiratory distress syndrome (RDS) is one of the most frequent causes of mortality and morbidity in neonates. High flow nasal canule (HFNC) is a step ladder modality of alternative oxygen therapy for weaning to reduce the workload of breathing and the need for intubation. Objective To identify the risk factors contributing to weaning failure from continuous positive airway pressure (CPAP) to HFNC in neonates with RDS. Methods This study was a retrospective observational study in neonates aged less than 36 weeks weighing less than 2500 grams who underwent CPAP to HFNC weaning from 2019 to 2021 in Dr. Kariadi Hospital, Semarang, Central Java, Indonesia. Results There were 108 patients included in this study. Our bivariate analysis found significant differences in gestational age, age at the start of weaning, body weight at the start of weaning, FiO2 levels, history of maternal chorioamnionitis, patent ductus arteriosus (PDA), anemia, apnea of prematurity (AOP), and sepsis in neonates with RDS. Multivariate analysis showed that the most dominant factors were FiO2 levels of more than 25% at the start of weaning (OR11.16; 95%CI 1.83 to 63.12; P=0.009), anemia (OR 7.70; 95%CI 1.39 to 42.67; P=0.019), AOP (OR 19.64; 95%CI 4.27 to 90.35; P<0.001), and sepsis (OR 10.93; 95%CI 2.37 to 45.53; P=0.002) Conclusion FiO2 setting of more than 25% at the start of weaning, anemia, AOP, and sepsis produce a significant probability of HFNC weaning failure.